2005
DOI: 10.1128/jb.187.18.6370-6378.2005
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of the N-Terminal Domain of ExeA: a Novel ATPase Involved in the Type II Secretion Pathway of Aeromonas hydrophila

Abstract: Aeromonas hydrophila secretes a number of degradative enzymes and toxins into the external milieu via the type II secretory pathway or secreton. ExeA is an essential component of this system and is necessary for the localization and/or multimerization of the secretin ExeD. ExeA contains two sequence motifs characteristic of the Walker superfamily of ATPases. Previous examination of substitution derivatives altered in these motifs suggested that ATP binding or hydrolysis is required for ExeAB complex formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…novicidia uses a T2SS that even lacks the GspLMC components to export chitinases, proteinases, and ␤-glucosidases (17). The presence of two ATPases in E. minutum, which are typical for T4P, does not necessarily argue against a T2SS; the T2SS of Aeromonas hydrophila also has two ATPases, and they are thought to increase the efficiency of the secretory process (47).…”
Section: Vol 75 2009 Genomic Analysis Of Elusimicrobium Minutum 2845mentioning
confidence: 99%
“…novicidia uses a T2SS that even lacks the GspLMC components to export chitinases, proteinases, and ␤-glucosidases (17). The presence of two ATPases in E. minutum, which are typical for T4P, does not necessarily argue against a T2SS; the T2SS of Aeromonas hydrophila also has two ATPases, and they are thought to increase the efficiency of the secretory process (47).…”
Section: Vol 75 2009 Genomic Analysis Of Elusimicrobium Minutum 2845mentioning
confidence: 99%
“…The GspAB Ah complex has been demonstrated to be required for the localization and multimerization of the GspD secretin multimer in the outer membrane of A. hydrophila (3). We have also shown that the GspA Ah cytoplasmic domain is a novel ATPase (46) and have confirmed the function of a peptidoglycan-binding site in the GspA Ah periplasmic domain as being required for the assembly of the secretin multimer (17,25). Thus, our working hypothesis is that the GspAB complex in some way modifies or organizes the peptidoglycan to allow assembly of the GspD secretin, a function presumably necessitated by the 50-kDa size constraint imposed by the peptidoglycan mesh (9).…”
mentioning
confidence: 67%
“…6) in a dose-dependent manner. Since GspAB functions as a heteromultimeric complex (46), this phenotype was likely caused by a dominant negative effect of GspAB Vc whereby the assembly of an inactive heteromultimeric complex composed of GspAB Ah and GspAB Vc reduces the ability of the strain to assemble a functional secretin multimer and, thus, secrete T2SS substrates into the growth medium. The dominant negative effect of GspAB Vc expression is consistent with the ability to inactivate the function of a multimeric protein by the expression of a mutant subunit in trans, a hallmark of multisubunit proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The periplasmic domain of ExeA has a peptidoglycan (PG)-binding domain that has been shown to bind PG from A. hydrophila, Escherichia coli, and Bacillus subtilis (20). Interaction with PG results in multimerization of ExeA in vitro, and in vivo ExeAB assembles into large complexes of up to 12 monomers of each protein (20,21). Point mutations in conserved residues within the PG-binding domain of ExeA demonstrated that PG binding is required for ExeD assembly (20).…”
mentioning
confidence: 99%